Analysis of the Fama and French three factor model on ASEAN markets. - Phua, Cindy Boon Ling. (2009)
The Fama and French three factor model introduced two variables (size and book to market value) to capture the cross-sectional variations of stock returns in the US market. This paper seeks to extend this finding to the ASEAN markets, namely the Singapore, Malaysia, Thailand and The Philippines equity markets. We make comparisons to the CAPM model and identify a fourth Liquidity Premium factor to investigate the effects on the explanatory powers of the three factor model. We document that while the US markets possess size and PB effects, we fail to observe similar phenomena in ASEAN markets. Also, time series and cross-sectional regression tests show that the CAPM, the Fama and French three factor model and the Four Factor Model have limited power to explain the excess equity return in ASEAN markets.